Comparative Study of Synchronous VS Asynchronous Distance Learning - Herdi, Herdi; Khalil, Ziad; Mansour, Nadine (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2025)
The evolution of distance learning has led to the widespread adoption of synchronous and asynchronous learning models, each offering unique advantages and challenges for students and educators. Synchronous learning provides real-time interaction, fostering immediate feedback and engagement, while asynchronous learning offers flexibility, enabling students to learn at their own pace. Understanding the effectiveness of these two models is essential for optimizing digital education strategies in higher education. This study aims to compare the impact of synchronous and asynchronous learning on student engagement, knowledge retention, and academic performance. A mixed-methods research design was employed, integrating quantitative analysis of student achievement data with qualitative insights from learner surveys and instructor interviews. Findings indicate that synchronous learning enhances real-time engagement and collaboration, whereas asynchronous learning promotes independent learning and accommodates diverse schedules. Statistical analysis reveals that both models contribute to academic success, but their effectiveness varies based on learner preferences, course design, and technological access. The study concludes that a blended approach, combining synchronous and asynchronous elements, may offer the most effective learning experience. Future research should explore long-term outcomes and best practices for integrating both models in diverse educational contexts.